The Role of Islamic Religious Education Teachers in Instilling Students Religious Character at Darul Ulum Sekampung Middle School - Rohmah, Khoiru; Hernisawati, Hernisawati; Hayati, Rina Mida (International Journal on Advanced Science, Education, and Religion, 2025)
religious education knowledge in the learning process, but also to carry out other efforts that can help achieve the goals of Islamic religious education. So that religious character can always be ingrained in students. So that Islamic religious education teachers can more easily instill religious character in students. This research method uses descriptive field research methods. This article explore the role of islamic religious education teachers in instilling students religious character at darul ulum sekampung middle school. The research samples were the school principal, Islamic religious education teacher and 5 students. In this research, researchers used several data collection tools, namely through observation, interviews and documentation. This research uses triangulation of sources and methodology to ensure the authenticity of the data. The results show that Islamic religious education teachers have carried out their role well in instilling religious character in students. Students become more orderly in carrying out religious activities at school, such as midday prayers and noon prayers in congregation at the mosque